The Effect of Numeracy Level on Completeness of Home Blood Pressure Monitoring - Rao, Vishal N. (J Clin Hypertens (Greenwich), 2014)
Home blood pressure monitoring (HBPM) readings predict the increased risks of cardiovascular events and end‐organ damage independent of office blood pressure (BP). Numeracy (the ability to handle numbers) may limit the feasibility of patients' performing HBPM. The authors analyzed data from 409 adults recruited from 12 North Carolina primary care clinics who completed a three‐item numeracy assessment, the Rapid Estimate of Adult Literacy in Medicine–Short Form health literacy assessment, and HBPM over 2 weeks. Among the 409 participants, 73% were college graduates and 69% had adequate numeracy. Completion of HBPM was greater among those with adequate numeracy (96.2% vs 93.7%; P=.009) and did not correlate with health literacy scores. More participants with adequate numeracy reported completion of ≥85% of readings than those with low numeracy (95% vs 88%; P=.018). Adequate numeracy, but not high literacy, is associated with more complete HBPM reporting. Whether higher numeracy is associated with more accurate self‐reported readings is an area of future research.